Exploring the biological functions of vtRNA 1-1 - Wainwright, Thomas (2023)
RNA that is transcribed from the genome mainly consists of non-coding RNA (ncRNA) which is not translated into proteins. Several important biological processes are regulated by ncRNAs, these include regulation of gene expression at the transcriptional and post transcriptional levels together with regulating protein translation. One type of ncRNA short non-coding RNA (sncRNA) vault RNA 1-1 (vtRNA 1-1) has been shown to regulate autophagy and its role in regulating specific aspects of neurodevelopment is starting to be unravelled. We also turn our attention to another type of ncRNA - the long non-coding RNA (lncRNA) MALAT1 (metastasis-associated lung adenocarcinoma transcript 1) which has also been shown to regulate specific aspects of neurodevelopment therefore we aim to provide further insight into the biological functions of vtRNA 1-1 and MALAT1. In the first instance HeLa cells were transfected to overexpress vtRNA 1-1 and a manual count to quantify P62 puncta was untaken to assess whether overexpression of vtRNA 1-1 relative to 5SRNA had any effect on a marker of autophagic flux. In a separate set of experiments primary neuronal cells were transfected to overexpress and inhibit expression of vtRNA 1-1 and MALAT1, axonal growth rates were then subsequently monitored. Overexpression of vtRNA 1-1 in HeLa cells did not reveal any effect on the levels of P62 puncta and overexpression of vtRNA 1-1 in primary neuronal cells did not demonstrate any effect upon axonal growth. Inhibition of vtRNA 1-1 expression significantly reduced axonal growth rates as did inhibiting MALAT1 expression in the same system. Collectively, we have explored the biological functions of ncRNAs in the context of axon growth and provide a foundation for others to investigate further how exactly different types of ncRNAs exerts their effect(s).